1996
DOI: 10.2165/00007256-199621010-00003
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Isokinetic Dynamometry in the Assessment of Human Muscle Function

Abstract: Isokinetic dynamometry has become a favoured method for the assessment of dynamic muscle function in both clinical research and sports environments. Several indices, such as peak torque, are used in the literature to characterise individual, group or larger population performance via these sophisticated data acquisition systems. Research suggests that there are several competing demands on the design of the measurement protocol which may affect the measurement of isokinetic strength and subsequent suitability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
1
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(110 citation statements)
references
References 46 publications
5
100
1
4
Order By: Relevance
“…Prior to testing each subject underwent a 5 min warm-up period of aerobic ergometer cycling. The subjects were then ®xed to the testing apparatus, an (Gleeson & Mercer, 1996). The strength of m. quadriceps (extension) and of the hamstrings (¯exion) were measured.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to testing each subject underwent a 5 min warm-up period of aerobic ergometer cycling. The subjects were then ®xed to the testing apparatus, an (Gleeson & Mercer, 1996). The strength of m. quadriceps (extension) and of the hamstrings (¯exion) were measured.…”
Section: Methodsmentioning
confidence: 99%
“…Optimal functioning of the knee flexors in particular is considered fundamental to the prevention of ACL injury (Gleeson and Mercer 1996;Johansson et al 1991;Rees 1994), however, a limited time frame exists whereby potentially harmful dynamic forces must be overcome by the most rapid response of the neuromuscular system in order to protect ligamentous tissue against injury (Gleeson et al 1998a;Huston and Wojtys 1996;Mercer et al 1998;Shultz et al 2001). For the ACL, the time frame from the initial application of such forces to the complete rupture of the ligament has been estimated at 300 ms (Rees, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…These data are in agreement with others who have demonstrated a 53% decrease in elbow flexors after 100 repeated eccentric actions (Linnamo, Bottas, & Komi, 2000) and repeated actions of the knee extensors (Brown, Child, Day, & Donnelly, 1997;MacIntyre, Reid, Lyster, Szasz, & McKenzie, 1996). However, others have shown that repeated eccentric muscle actions are extremely fatigue resistant despite high force production (Emery et al, 1994;Hortobagyi et al, 1996;Tesch, 1990 It has been suggested that an ICC of 0.88 or above and CV not exceeding ± 6% demonstrates good reliability in isokinetic strength testing (Gleeson & Mercer, 1996). The relative reliability for the WFI and TFI in the current study are lower than this recommended value for both the knee extensors and flexors.…”
Section: Discussionmentioning
confidence: 99%